2016
DOI: 10.1186/s11671-015-1213-8
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Structure of Electron Bands in Double-Resonant Raman Spectra of Single-Walled Carbon Nanotubes

Abstract: Micro-Raman spectra of single-walled carbon nanotubes in the range of two-phonon 2D bands are investigated in detail. The fine structure of two-phonon 2D bands in the low-temperature Raman spectra of the mixture and individual single-walled carbon nanotubes is considered as the reflection of structure of their π-electron zones. The dispersion behavior of 2D band fine structure components in the resonant Raman spectra of single-walled carbon nanotube mixture is studied depending on the energy of excitating phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Furthermore, a detailed analysis of the G band line shape indicated that it was split into G − and G + components, once again providing evidence for the single-walled character of the material ( Figure 3 b) [ 37 ]. The shape of the G − component can determine the type of SWCNTs in resonance [ 38 , 39 ]. In this case, the SWCNTs revealed substantial semiconducting character, which made them ideal for doping.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a detailed analysis of the G band line shape indicated that it was split into G − and G + components, once again providing evidence for the single-walled character of the material ( Figure 3 b) [ 37 ]. The shape of the G − component can determine the type of SWCNTs in resonance [ 38 , 39 ]. In this case, the SWCNTs revealed substantial semiconducting character, which made them ideal for doping.…”
Section: Resultsmentioning
confidence: 99%
“…2 was caused by scattering by Brillouin zone center phonons, whereas the 2D-band (also referred to as G') has been observed when sp 2 carbons exist, and can be attributed to resonant Raman scattering processes. [52][53][54] The line shape and the relative intensity of the 2D-band can be used to determine the number and orientation of graphene layers in few-layered graphene samples (1-5 layers). 52 Indeed if the graphene is defect-free, the 2D-band is expected to have a high intensity and a sharp lineshape.…”
Section: Resultsmentioning
confidence: 99%
“…Some special laser lines should be chosen to enhance the 2D band when the bandgap is open to the visible and even ultraviolet range, similar to that in carbon nanotubes. 216,217 Furthermore, for defect-containing graphene in stage 2, I(2D) gradually becomes weaker. I(2D) can even become invisible for heavily disordered graphene.…”
Section: Raman Spectra Of Defect-containing Graphene Flakesmentioning
confidence: 99%